A COMPARATIVE STUDY ON THE EFFECTIVENESS OF ANGIOTENSIN CONVERTING ENZYME INHIBITORS (ACEIs) AND ANGIOTENSIN RECEPTOR BLOCKERS (ARBs) IN DIABETIC NEPHROPATHY IN TYPE 2 DIABETES MELLITUS PATIENTS - Senthilkumar, N.; A., Anandhasayanam; K., Mohammed Safil; S., Shemimol (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To observe the clinical outcomes on usage of angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in type 2 diabetic nephropathy patients. Methods: A total 70 patients diagnosed with diabetic nephropathy were treated with ACEIs or ARBs were enrolled in this study. The data was collected from the out patients and the physician. A data collection form was used for collecting patient data. The form was used to record the details of patient's demographics, history of diabetes mellitus, duration of diabetes mellitus co morbidities, food habits and laboratory parameters such as serum creatinine, HbA1c and all the relevant things. The study has obtained ethical clearance from the institution ethics committee (IEC). Results: The study showed middle aged patients were more prone to diabetes and pre-existing hypertension is a major risk factor for diabetic nephropathy. Majority of the patients had long duration of diabetes mellitus which indicates the strong relation between duration of diabetes mellitus with diabetic nephropathy. Compared to ACE inhibitors, ARBs decreased the level of renal parameters. This reveals the better reno-protective effect of ARBs over ACE inhibitors. ARBs had more beneficial effects in reducing the major risk factor like proteinuria in diabetic nephropathy. A considerable reduction in HbA1c values were also observed in patients using ARBs. Conclusion: While comparing the improvement in proteinuria and the laboratory outcomes, ARBs were beneficial relatively to the ACEs in patients with diabetic nephropathy. Â